An Updated Demographic Profile of Orthopaedic Surgery Using a New ABOS Data Set - Lindsey S. Caldwell, MD; Natalie Glass, PhD; Gregory P. Guyton, MD; David W. Elstein, BA; Charles L. Nelson, MD, FAOA (JBJS Open Access)
Introduction:. The orthopaedic surgery physician workforce is predominately White and male and has been identified as the least diverse medical specialty. Increasing efforts toward diversification within orthopaedic surgery are underway. Evaluating the effectiveness of these programs requires a thorough understanding of the current demographic profile of the profession. Methods:. The American Board of Orthopaedic Surgery (ABOS) is the leading board certification organization for orthopaedic surgeons in the United States. The ABOS began collecting self-reported race/ethnicity and sex/gender data of its examinees and diplomates in 2017. This new data set of ABOS was analyzed to describe both the current demographic profile of orthopaedic surgery and trends over time. Underrepresented minority (URM) was defined as a group that is less well represented in orthopaedic surgery than in US census data and includes female, American Indian or Alaska Native, Black or African American, Hispanic/Latino, and Native Hawaiian or Other Pacific Islander categories. Results:. Of the 21,025 currently practicing ABOS diplomates with time-limited ABOS certificates (issued since 1986), 19,912 (94.7%) provided sex/gender data, and 19,876 (94.5%) provided race/ethnicity data. Approximately 84.78% selected male and 8.43% female. The majority identified as White (73.67%), whereas 16.35% selected a URM race/ethnicity category. There have been significant increases in the proportions of female (odds ratio [OR] = 4.72, 95% confidence interval [CI] = 3.64-6.11, p < 0.001) and URM (OR = 2.31, 95% CI = 1.80-2.96, p < 0.0001). Diplomates among orthopaedic surgeons attaining ABOS board Diplomates from 1989 to present. Among the subspecialties, pediatric orthopaedics reported the highest percentage of females (30.4%). Spine had both the lowest percentage of females (2.63%) and the highest percentage of URMs (8.97%). Sports had the lowest percentage of URMs at 5.63%. Conclusion:. Orthopaedic surgery in 2023 remains largely White and male. However, there have been promising trends toward diversification of orthopaedic surgery both in terms of gender and race/ethnicity. Specialties within orthopaedics have a wide variety of demographic profiles. Level of Evidence:. Level IV Retrospective Cohort Study. See Instructions for Authors for a complete description of levels of evidence.